PERANAN GAYA KEPEMIMPINAN YANG EFEKTIF DALAM UPAYA MENINGKATKAN SEMANGAT DAN KEGAIRAHAN KERJA KARYAWAN BAGIAN PEMASARAN - Siti Almaidah (STIE Atma Bhakti, 2015)
In every organization, one of the important elements in managing management, is a matter of leadership. The role of the leader is decisive in an effort to reach the target which has been set. The effectiveness of a leader is determined by its ability to influence and direct members of organization. The effectiveness of a leader is also determined by its ability appropriately in anticipation of the nature of the conditions it faces, both the conditions contained within the organization as well as conditions outside the organization. This study aims to examine and analyze the influence of autocratic, democratic, and free leadership style to the spirit and enthusiasm of employees at P.T. Gudang Garam Bojonegoro, and testing the tendency of leadership styles to be applied in an effort to improve the spirit and enthusiasm of employees. The results of testing the quality of the data obtained that all items of question on each variable shows valid and reliable results. While the hypothesis testing obtained that the style of leadership autocratic, democratic, and free have a positive and significant influence on the spirit and enthusiasm of employees. Partial tests show that democratic leadership style has the greatest influence on the spirit and enthusiasm of employees. In this study also disclosed that an effective leadership style is leadership that is tailored to the situation and conditions of the people he leads. Indications of the decline in the spirit and enthusiasm of employees of work is showed by high levels of absenteeism and employee movement. This arises as a result of undesirable leadership Keywords: the style of autocratic leadership, the style of democratic leadership, the style of free leadership, the spirit and enthusiasm of employees